PENGARUH UPAH DAN PRODUKSI TERHADAP PENDAPATAN KELUARGA PETANI JAGUNG DI KECAMATAN LUBUK BASUNG KABUPATEN AGAM - Yaumil Khairiyah SY; Andis Febrian (Adisam Publisher, 2024)
The background to this research is that wages continue to increase and increase every year, while the level of production and prices in farming do not always increase, sometimes the price of corn production decreases and even experiences price fluctuations. Apart from wages which inc /rease every year, another problem stems from the price of seeds which continues to increase every year. Many corn farmers complain that wages continue to increase while production is not appropriate and not balanced with wages. The farming business actors also said that the income was not enough to meet their needs and some even said that they had no profit or even a return on capital. This research aims to find out and analyze how much influence wages and production have on the income of corn farming families in Lubuk Basung sub-district, Agam district. This research is quantitative research. using a research instrument in the form of a questionnaire with a sample of 40 respondents. Data analysis techniques include instrument testing (validity test and reliability test), classical assumption tests (normality test, heteroscedasticity test, multicollinearity test, and autocorrelation test), hypothesis testing (coefficient of determination test, multiple linear regression analysis, T test, and F test. The results of this research show that there is an influence of wages and production on the income of corn farmer families, obtained by the calculated f value (17.926) ≥ f table (4.105) and the sig value (0.000) ≤ 0.05. It was concluded that wages and production had an influence on the income of corn farming families.